Pengembangan Pribadi Islami dalam Pendidikan Kewirausahaan di SD Islamic Center Samarinda - Kolik, Abdul (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
Education is carried out not only through the delivery of lesson materials and the completion of assignments in the classroom, but also through projects outside the classroom, in order to foster students' abilities and the growth of life experiences within the community. Entrepreneurship education becomes an attractive option for providing valuable experiences for students. This research explores the development of Islamic personal character through entrepreneurship education at SD Islamic Center Samarinda. Using a descriptive qualitative method involving observations, interviews, and documentation, the study finds that entrepreneurship activities, specifically through the "Market Day" event, cultivate entrepreneurial spirit and Islamic values among elementary students. The findings reveal that Market Day activities instill essential traits such as responsibility (Mas'uliyyah), honesty (Sidq), hard work, and perseverance. Students are taught to apply Islamic principles in trade, such as fair pricing, truthfulness in product descriptions, and maintaining ethical conduct. The integration of entrepreneurship education with Islamic character development offers a holistic approach, preparing students not only with basic economic skills but also with strong Islamic morals. This study suggests that entrepreneurship education from an early age can effectively shape students' independence, creativity, and Islamic identity.